The Interaction between State Law and Customary Law in the Management of Ulayat Land in West Sumatra - Hairi, Alvin; Rahman, Taufiqur; Atmanegara, Aldi; Perdana, Roland Anggala; Yunanda, B.R.E (The Future of Education Journal, 2025)
The background of this study stems from the socio-legal reality in Dharmasraya Regency, West Sumatra, where the existence of ulayat land, as part of the Minangkabau customary heritage, is increasingly challenged by state legal interventions—particularly in the context of development, industrial expansion, and land certification programs. While indigenous communities still uphold customary legal systems in managing ulayat land, the state introduces positive legal regulations that often neglect local wisdom and communal ownership values. This has led to issues such as agrarian conflicts, loss of collective land rights, and marginalization of adat institutions. The aim of this research is to explore the interaction between state law and customary law in the management of ulayat land in Dharmasraya, and to identify patterns of harmony or conflict that arise in practice. This is a qualitative study using a case study approach. Data were collected through in-depth interviews with traditional leaders, nagari government officials, land agency representatives, and local residents, supported by field observations and document analysis of relevant legal frameworks and regional regulations. Findings reveal that in several nagari such as Koto Padang and Sungai Duo, the management of ulayat land still relies heavily on kinship-based collective decision-making. However, this is gradually being eroded by the implementation of the Systematic Land Registration Program (PTSL), which promotes individual ownership. Interviews show that 60% of traditional leaders feel their authority is being diminished, while 70% of community members admit they do not fully understand the legal implications of ulayat land certification. A duality of authority has emerged, complicating mediation in disputes between indigenous groups and external investors. In conclusion, the interaction between state and customary law in Dharmasraya remains imbalanced and largely disharmonious, with state law dominating land administration practices. This research recommends the development of policies that contextually integrate customary norms into the national legal framework, as well as the empowerment of local customary institutions. These efforts are essential to ensure the sustainable management of ulayat land as both a cultural identity and an economic resource for indigenous communities.